A new species of Tropidopedia from the Amazon rainforest, Brazil (Hymenoptera: Apidae), with a revised phylogenetic overview of the genus - Mahlmann, Thiago; Oliveira, Marcio L. De (Zootaxa, 2015)
We describe a new species of the bee tribe Tapinotaspidini, Tropidopedia guaranae Mahlmann & Oliveira sp. n. from the Amazon rainforest, Amazonas, Brazil. We emend the phylogenetic tree of Aguiar & Melo (2007) to include the new species and comment upon some characters presented by those authors.